Pengaruh Serat Ban Bekas dan Abu Batu Bara Terhadap Kuat Tarik Beton - Bunyamin Bunyamin; Imransyah Idroes; Reska Wahyu Fauzha (Universitas Teuku Umar, 2023)
In today's modern era, technological developments are needed to increase development in all fields. The manufacture of concrete can use partial cement substitution materials through the use of industrial by-products such as fly ash and fiber waste from used tires. The benefit of this research is to develop knowledge about concrete technology. The method used in this research is the ACI 211.1-91 (American Concrete Institute) and ASTM (American Society for Testing and Materials) methods with variations in the addition of used tire fiber by 0%, 5%, 10%, 15%, and 5% addition of fly ash from the weight of cement in each variation. The test object used is a cylinder with dimensions of 15 cm x 30 cm with a total of 20 test objects, the planned concrete quality is 17.00 MPa. The tensile strength of concrete test was carried out at the age of 28 days. The results of this study are that concrete with a variation of 0% produces a tensile strength of 2.32 MPa; while the tensile strength with variations of 5%, 10% and 15% were 2.71 MPa, 2.50 MPa and 2.41 MPa. The tensile strength of concrete using tire fiber waste and fly ash increases compared to normal concrete.